Mourning after: Stories of sorrow and redemption - Crisostomo, Iris Sheila G. (Animo Repository, 2003)
This writing project is a collection of short stories that attempts to explore the concept of sorrow as brought about by various absences and losses in our lives, sorrow as a test of a character's strength or frailty and sorrow as a possible vehicle to self-redemption. The project consists of one (1) published short story and four (4) new and unpublished short stories. It makes use of the philosophical framework of Sigmund Freud's theories in Psychoanalysis. In his article, Mourning and Melancholia, Freud identified absences or losses of a person or a cherished idea as the root cause of sadness and sorrow of our lives. We are constantly beset by sorrow and we react to it in different ways.